Color Tunable Emission and Oxygen Sensing from a Discrete Europium−Pyrene Assembly - O'Neil AT; Pope J; Harrison JA; Kitchen JA (Wiley-VCH GmbH, 2023)
We report the synthesis of a new pyrene, dipicolinic acid-based ligand (L1H) and its corresponding multi-emissive and multifunctional europium complex [Eu(L1)3] that is capable of single component color switchable emission from red to blue and also white. At high concentration (10 mM) the single component system results in near pure white emission (CIE coordinates x,y=0.329, 0.324). Furthermore, the system showed ratiometric oxygen sensing with oxygen significantly quenching the pyrene centered emission but not the Eu3+ emission, resulting in an overall emission color change from blue to red on increasing oxygen content.